Interlinked population balance and cybernetic models for the simultaneous saccharification and fermentation of natural polymers / Ho Yong Kuen - Ho, Yong Kuen (2015)
The generation of important and useful products (e.g. ethanol, lactic acid etc.) through microbial fermentation often involves the breakdown of complex polymeric feedstock such as starch and cellulose through enzymatic scissions followed by subsequent metabolic conversion. The interplay between the kinetics of enzymatic depolymerization and the response of the microbes towards changes in the abiotic phase is critical for the adequate description of such a complex process. In this work, two unrelated frameworks, i.e. the Population Balance Modelling (PBM) and the Cybernetic Modelling (CM) were interlinked to model such a system. Specifically, the PBM technique was used to describe the enzymatic depolymerization whereas the CM framework was used to model the microbial response toward complex environmental changes. As the enzymes required to break down polymeric substrates are produced by the microbes, a more general treatment of the secretion of extracellular enzyme was also proposed in the CM model. In the course of interlinking the two frameworks, the numerical techniques for solving Population Balance Equations (PBEs) were explored. In this regard, the Fixed Pivot (FP) technique was successfully modified to solve chain-end scission which resembles the action of enzyme which removes a monomer from the end of a polymer chain. This method was further extended to include random scission (resembling the action of enzyme which randomly hydrolyzes the bond of a polymer chain) and mixed scission involving both modes. Simulation results showed that the FP technique was able to solve chain-end scission and simultaneous random and chain-end scissions to a high degree of accuracy using 0.02% and 1.2% of the time required for solving the exact case respectively. One notable feature of the interlinked framework is the flexible linkage, which allows the individual PBM and CM components to be independently modified to the desired levels of detail. The interlinked PBM and CM framework was implemented on two case studies involving the Simultaneous Saccharification and Fermentation (SSF) of starch by two recombinant yeast strains capable of excreting glucoamylase alone or together with α-amylase. The simulation results revealed that the proposed framework captured features not attainable by existing approaches. Examples of such include the ability of the model to indicate (in case study one) that an appropriate amount of glucose (7 g) mixed with starch (30 g) as initial substrates yielded an optimum productivity of ethanol. Not only that, the model showed (in case study two) that SSF is indifferent to the type of starch when both enzymes are present as opposed to when only glucoamylase is present, where the time required for ethanol concentration to peak differed by more than 30 hours between different starches. Thus, the effect of various enzymatic actions on the temporal evolution of the polymer distribution and how the microbes respond to the initial molecular distribution of the polymers can be studied. Such a framework also enables a more molecular and fundamental study of a complex SSF system, a feat which heretofore was unattainable by existing SSF models.